Acrylamide Contamination, Shelf-Life and Sensory Properties of Puffed Potato Starch Chips Deep-Fried in Rapeseed Oil-Based Oleogels - Sylwia Onacik-Gür; Stanisław Ptasznik; Anna Zbikowska; Katarzyna Marciniak-Lukasiak (Applied Sciences)
The utilization of oleogels as a frying medium has been studied in recent years. In this research, rapeseed oil structured by rice bran wax (RW) and beeswax (BW) was used as a frying medium for the production of puffed potato starch chips. Chips and their lipid fractions were analyzed for their changes in quality during 9 weeks of storage. It was observed that the addition of beeswax contributed to the increase in the acid value of the puffed chips’ lipid fraction. The level of unsaturated fatty acids decreased in all fried products; however, the lowest changes were observed for products fried in RW oleogel. The presence of waxes slowed down oxidation which was indicated by the lowering of the peroxide value from 67.84 (for rapeseed oil) to 52.62 meq O2/kg (BW oleogel) at the end of storage. A similar situation was observed in the case of changes in the hardness and water activity of puffed chips. The addition of waxes to the frying medium contributed to a significant reduction in oil uptake in the puffed chips, where products fried in oil with RW fat were 17.7% lower than the control sample. The addition of BW 5 g/1 L of frying oil can increase the acrylamide content from 57 μg/kg for rapeseed oil to 97 μg/kg. Sensory evaluation of the puffed chips showed no statistically significant differences between products fried in oil with or without the addition of waxes.